Gone - Grant, Michael, 1954- (New York : HarperTeen, 2008)
In the blink of an eye, everyone disappears. Gone. Except for the young. There are teens, but not one single adult. Just as suddenly, there are no phones, no internet, no television. No way to get help. And no way to figure out what's happened. Hunger threatens. Bullies rule. A sinister creature lurks. Animals are mutating. And the teens themselves are changing, developing new talents -- unimaginable, dangerous, deadly powers -- that grow stronger by the day. It's a terrifying new world. Sides are being chosen, a fight is shaping up. Townies against rich kids. Bullies against the weak. Powerful against powerless. And time is running out. On your birthday, you disappear just like everyone else ...
Young Adult.
620
Accelerated Reader/Renaissance Learning
Reading Counts!
Keywords: Disappearances (Parapsychology) -- Juvenile fiction; Good and evil -- Juvenile fiction; Regression (Civilization) -- Juvenile fiction; Leadership in adolescents -- Juvenile fiction; Supernatural -- Fiction; Good and evil -- Fiction; Survival -- Fiction; Disappearances (Parapsychology); Good and evil; Leadership in adolescents; Regression (Civilization); California -- Juvenile fiction; California; Paranormal fiction; Young adult fiction; Fiction; Juvenile works; Paranormal fiction; Young adult works